Cultivating connections: a transformative journey in international community service / Hafizy Akmal Hamzah - Hamzah, Hafizy Akmal (Faculty of Pharmacy, 2023)
The expedition from the Faculty of Pharmacy from UiTM to Universitas Pakuan, Bogor, Indonesia demonstrated the effectiveness of international exchange and community engagement. This expedition was not just a mere visit but a transformative experience, forging connections and fostering a deeper understanding of the world around us.